3D Scanner App For New Product Development Due To Covid-19 Endemic - Habidin, Mohamad Ridzuan (Universiti Sains Malaysia, 2022)
The events of 2020 made the term "pandemic" popular in homes around the world. We've been living with COVID-19 for over two years, and the virus is currently in an endemic phase. The endemic indicates that the virus will remain among us and will be treated as a common illness. People are finding it difficult to adjust to the spread of the COVID-19 virus. As a result, a new product for civilians that will benefit and add value to society in the event of the COVID-19 outbreak should be produced. As a result, there is room for such a product to be developed and sold. A survey has been completed for the client, and the consumer will be required to fulfil all their demands and difficulties. The outcome will be analysed, and the tally with the limitation of movement has developed a new approach to understand the available product by implementing the 3D scanner application, where reverse engineering will be performed on the target part model. The results reveal that the survey gave a few arguments, which allow for product development. With the use of a 3D scanner application, a new tissue holder was constructed. Several studies have been undertaken to determine how the tissue holder will benefit the client based on its usefulness. This project is the initial step toward creating a completely functional new design of tissue holder that corresponds to the current scenario using a 3D scanner.